Activation of the cGAS–STING signaling pathway in adenomyosis patients. Issue 3 (19th May 2021) - Lin, Yun; Wang, Luying; Ye, Mingzhu; Yu, Ke‐nan; Sun, Xin; Xue, Min; Deng, Xinliang
Abstract: Objective: Adenomyosis is characterized by the presence of endometrium or endometrium‐like glands and stroma within the myometrium. In this study, we aimed to investigate whether the cGAS–STING pathway was activated and correlated with clinical outcomes in adenomyosis patients. Materials and Methods: Twenty patients diagnosed with adenomyosis and 10 patients diagnosed with cervical intraepithelial neoplasia grade 3 (CIN‐3) but no adenomyosis were enrolled in this study. Specimens were collected during surgery from August 2017 to December 2017 at Third Xiangya Hospital. The messenger RNA (mRNA) and protein levels of key cGAS–STING pathway factors in uterine tissue were detected by real‐time reverse‐transcription polymerase chain reaction and immunohistochemistry, respectively. The correlations of gene expression and clinical outcomes, including dysmenorrhea and uterine volume, were analyzed. Results: The cGAS, STING, TANK‐binding kinase 1 (TBK‐1), interferon‐α (IFN‐α), IFN‐β, and tumor necrosis factor‐α (TNF‐α) mRNA and protein levels in the ectopic endometrial tissue from adenomyosis patients were significantly higher compared with that from the controls in endometrium ( p < .05). cGAS and STING gene expression were correlated with TBK‐1, IFN‐β, and TNF‐α expression ( p < .05). Importantly, TBK‐1 and TNF‐α expression were correlated with the clinical outcome of dysmenorrhea ( p < .05). Conclusion: Our study reveals that the cGAS–STING pathway is activated in adenomyosis patients and its activation is subsequently correlated with clinical outcomes, which suggests that the cGAS–STING pathway may contribute to adenomyosis pathogenesis. Abstract : Representative pelvic magnetic resonance imaging (MRI) from the control and adenomyosis patients. A. In a control patient (control), the MRI picture shows the normal uterine, with dimensions of a 45.6‐mm length and 43.1‐mm width crossing the whole uterus. B. In an adenomyosis patient (Aden.), the MRI scan shows typical focal adenomyosis, with a 40.6‐mm length and 56.9‐mm width of pathological foci located in the uterine junctional zone (indicated with a red star).